Millennial spring : designing the future of organizations - Grace, Miriam; Graen, George B. (LMX leadership., 2014)
Our corporate dominated world is resisting the best efforts of the "under 30s" to shape it into the information age. This eBook contains information about what the careers of the "under 30s" corporation will become. This was done examining recent trends in careers of "growing-tip" companies like Apple, Boeing, Microsoft and US and international design schools.The world of careers is changing fast, and the millennials - the generation of people who became adults around 2000, or in the decade or so after - have been right in the middle of it. From Independence Square in Kyiv to the streets of Caracas, from Taksim Square in Istanbul to Zuccoti Park in New York, and from Silicon Valley to Wall Street, it's the 30-and-under crowd courageously leading the quest for different ways. Less invested in past approaches, tech-savvy to a fault, and painfully aware of the challenges left to them by earlier generations, they're not willing to "settle" - to make the same compromises (and mistakes) they think their parents made. And although they sometimes get rapped for being self-centered, all the evidence I see - and I've taught thousands of them on two continents, and even have one in my own family -- suggests that the millennials represent real hope for the future. Please consider this a call to all millennials - here, in the pages of this book, are some of the means. Get out there and create the under-30s revolution. Solve the problems your parents couldn't. Do it together, with a conscientious eye to what works for all involved. Get out there and save the world.